(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: Describe the status of breastfeeding mothers after giving birth during their hospital stay at the Department of Obstetrics and Gynecology at Hanh Phuc International Hospital, Binh Duong province and analyze some related factors. Research method: An analytical cross-sectional study was performed on 270 vaginal and cesarean deliveries, using a checklist of early breastfeeding and breastfeeding during the hospital stay and interviews to identify associated factors. Results: The rate of infants being breastfed early in the first hour after birth reached 86.7%, and the rate of infants exclusively breastfed during the hospital stay was 57.8%; Some of the factors linked to early breastfeeding after birth are maternal education, pre-pregnancy, antenatal classes, and delivery method. Some factors related to exclusive breastfeeding during library time are attending pre-production and birth methods classes, having family support, and breastfeeding properly. Conclusion: The majority of mothers giving birth at Hanh Phuc International Hospital have started breastfeeding their babies soon after birth, but the percentage of mothers who exclusively breastfeed their babies during their postnatal hospital stay is not high. The rate of exclusive breastfeeding during the postpartum hospital stay in the group that participated in antenatal training was 1.2 times higher than that in the group that did not receive the training. The rate of exclusive breastfeeding during the postpartum hospital stay was lower in the cesarean section than in the vaginal delivery group. The rate of exclusive breastfeeding during postpartum hospital stay was 1.97 times higher in the group with family help in breastfeeding compared to the group without help…